STRATEGI BRANDING DIGITAL: PEMANFAATAN MEDIA SOSIAL DALAM PROMOSI PULAU TAMPELEKAN DI DESA SIMATANG TANJUNG - Sitti Rahmah; Arqam Samsuriadi; Sri Wulan; Taufik Hidayat; Nursam Nursam (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Tourism is an important sector that supports the economy in a region. One of the tourist destinations in Simatang Tanjung Village, North Dampal District, is Tampelekan Island. Few people outside know this destination; besides its location in a remote village, there is still a lack of manual and digital publications regarding this tourist attraction. Community Service Program students learned about the existence of Tempelekan Island tourist attraction when they first visited Simatang Tanjung Village. Next, direct observations were conducted on Tempelekan Island to identify its various potentials, including the richness of flora and fauna that are still natural and well-preserved. Based on the results of these observations, students then carried out promotional activities for Tampelekan Island tourism by focusing promotional efforts through social media, especially the Instagram platform. This promotional activity aimed to attract visitors to Tampelekan Island, in Simatang Island